Infrastruktura techniczna jako czynnik determinujący rozwój przedsiębiorczości (na przykładzie gmin województwa zachodniopomorskiego) - Tomaszewski, Marek (Technical Infrastructure as a Factor Determining Enterprise (Case of Communes in Zachodniopomorskie Province), 2006)
The comparison of the data presented in parts 2 and 3 referring to selected elements of technical infrastructure with the level of residents' enterprise in various areas (urban, urban-rural and rural) reveals a certain regularity: in areas where technical infrastructure is more developed, the level of private initiative and enterprise is higher and vice versa. There is a feedback between these two categories, such that infrastructure enhances business activities of local residents and, in turn, the residents' enterprise indirectly affects the level of technical infrastructure.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 443-448